2016
DOI: 10.5708/ejmh.11.2016.1-2.6
|View full text |Cite
|
Sign up to set email alerts
|

Body Awareness, Mindfulness and Affect: Does the Kind of Physical Activity Make a Difference?

Abstract: The aim of this cross-sectional study is to explore expected differences in the connection between particular physical activities and positive and negative affect, body awareness or mindfulness. Additionally, we describe the so-called tingling phenomenon (i.e. skin-related sensations evoked by focusing on a body part) in terms of prevalence, gender differences and psychological concomitants. A total of 1,057 individuals (331 male; mean age: 30.6 ± 10.17 years) practicing yoga, Pilates training, kung fu, aerobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 18 publications
(14 reference statements)
5
23
1
1
Order By: Relevance
“…The positive association between subjective well‐being and interoceptive sensibility (i.e., the subjective or perceived aspect of interoception) replicates the findings of previous studies (Hanley et al, ; Tihanyi, Böőr, et al, ; Tihanyi, Sági, Csala, Tolnai, & Köteles, ). One explanation is that better psychological functioning and lower levels of perceived stress enable healthy individuals to allocate more attentional resources to various stimuli, including information originating in the body (Köteles et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…The positive association between subjective well‐being and interoceptive sensibility (i.e., the subjective or perceived aspect of interoception) replicates the findings of previous studies (Hanley et al, ; Tihanyi, Böőr, et al, ; Tihanyi, Sági, Csala, Tolnai, & Köteles, ). One explanation is that better psychological functioning and lower levels of perceived stress enable healthy individuals to allocate more attentional resources to various stimuli, including information originating in the body (Köteles et al, ).…”
Section: Discussionsupporting
confidence: 87%
“…Each of the items is stated inversely using a six-point Likert scale (from almost always to almost never) asking the respondents of how often they find themselves acting automatically, inattentively or being preoccupied. The Hungarian version had a good internal consistency (Cronbach's alpha = 0.78) in earlier studies (simor et al 2013;tiHanyi et al 2016). In the present study, the internal consistency of the scale was 0.86.…”
Section: Questionnairessupporting
confidence: 65%
“…Advanced hatha yoga practitioners showed higher levels of mindfulness than beginners (BrisBon & LoWery 2011), and in a pilot study of a four-month residential yoga group, mindfulness was found to mediate the group effect on quality of life, compared to matched controls (gard et al 2012). In a cross-sectional study, however, no connection was found between mindfulness and frequency of yoga practice, and advanced yoga practitioners showed no higher levels of mindfulness than those practicing aerobic (tiHanyi et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations